The ‘Real’ Pakistan in Uzma Aslam Khan’s The Geometry of God (2007): A Testimony of Blasphemy - Ana Ashraf (Angles)
Since their widespread implementation and amendment in the 1980s by Muhammad Zia-ul-Haq, blasphemy laws have been used in Pakistan to supress freedom of speech and to create an environment of terror, fear, and subjugation. Islamist political parties on the right side of the spectrum in alliance with the military establishment ensure that resistance against these laws both judicially and socio-politically becomes almost unfeasible. Those who do have a chance to be released from the charges are faced with death threats and often become prey to homicide or mob lynching. In such a scenario, literature can and must offer an alternative imaginative space where constructive dialogue is made possible and where some form of healing is offered to the victims. It, therefore, becomes incumbent to understand the way in which Uzma Aslam Khan’s The Geometry of God (2017) offers an alternative to the state led official narrative regarding issues of blasphemy, freedom of expression and creative thought in relation to Pakistani identity. The Geometry of God deals with Pakistani history in the 1980s and ’90s under Zia-ul-Haq’s influence and legacy from three different narrator-perspectives and the (mis)use of blasphemy laws in Pakistan with respect to Zahoor, a palaeontologist. The book challenges the mainstream narrative about blasphemy as well as Pakistani history as it unfolds, and presents, instead, an alternative ‘real’ image of modern Pakistan which is more complex, polyphonic, and diverse. In this respect, this article demonstrates how Khan creates a larger alternative literary testimony within the novel through three narrator-characters as well as by employing various stylistic features. Indeed, the novel both mirrors and challenges the ‘official’ court testimony where Zahoor is silenced by false accusations against him in the name of blasphemy. Through a detailed analysis of the three narrators, this article shows how memories of past events are represented, including the way in which the literary form of the novel foregrounds the act of testimony.